Economic Literacy, Self-Control, Religiosity, and Consumption: A Mediation Study on Shopee Users’ Lifestyle - Lis Supriyadi; Rosana Eri Puspita (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2022)
This study explores the impact of economic literacy, self-control, religiosity, and lifestyle on consumption behaviour among Shopee customers. The research method utilizes path analysis to identify the influence of lifestyle variables that have been considered. This study’s regression analysis revealed that economic literacy, self-control, and religiosity negatively impacted consumptive behaviour. The variables of economic literacy, on the other hand, have a strong positive impact on lifestyle. Furthermore, self-control and religiosity have a negative and minor impact on one’s lifestyle. Lifestyle variable routes can mediate the influence of economic literacy on wasteful behaviour in the analytical test. On the other hand, lifestyle cannot mitigate the impact of self-control and religiosity on consumption.